Green Supply Chain Coordination During the COVID-19 Pandemic Based on Consignment Contract - Wang, Yi; Reivan Ortiz, Geovanny Genaro; Dextre-Martinez, William; Zhang, Liandi (Frontiers in Environmental Science, 2022)
The COVID-19 has further strengthened consumers’ online consumption habits. At the same time, online shopping brings a new boom for enterprises in avoiding risk and gaining profits in the pandemic. To investigate members’ profit obtained in the boom, we proposed a model containing one green products manufacturer and one e-commerce platform to achieve environmentally sustainable development. In the model, we studied each member and total channel’s performance based on the consignment contract. Comparing two channel’s results, we found that centralized channel can attract more profits, which will be beneficial to the research and development of green products. To mitigate conflicts of interest between the supply chain, we investigated the coordination between two members by Nash and Rubinstein bargaining contract. According to each member’s bargaining power and patience, the optimal platform usage rate is determined, the supply chain profits of both sides are allocated, green production’s research and development is promoted, and win-win situation is realized.